Marcadores osteogênicos e reprogramação epigenética durante a transição fenotípica do músculo liso vascular: da contração à calcificação - Feltran, Geórgia da Silva [UNESP] (2024)
The vascular system is responsible for transporting cells and nutrients throughout the body. It is a dynamic tissue with exceptional physiological activities, but which is subject to the installation of pathologies, such as vascular calcification. Vascular calcification is characterized as an ectopic deposition of inorganic calcium phosphate crystals in arterial tissue leading to a significantly increased risk of morbidity and further mortality. It is a pathology of multifactorial etiology, related to physiological and environmental causes and some authors have already highlighted that this condition recapitulates morphogenic events of osteogenesis. However, the molecular study still needs further investigation, especially bringing an epigenetic understanding of this environmental influence on the expression of genes involved in the process. In this context, the main objective of this study was to investigate whether epigenetic mechanisms are involved in the activation of osteogenic gene markers in smooth muscle cells during the calcification process. Primary Aortic smooth muscle obtained cells (AoSMC) were treated with medium containing an overload of calcium (2.7mM) and phosphate (2.6mM) for up to 3 days, when the samples were properly collected for analysis of protein content, gene expression, immunofluorescence, epigenetics and colorimetric assays. The results obtained in both Chapter 2 and Chapter 3 demonstrate an experimental model able for mimicking the calcifying environment of muscle cells in vitro. This could be proven because the VSMC used in the model expressed a molecular repertoire of osteogenic biomarkers, specifically RUNX2, Osterix, ALP and BSP over 72 hours in vitro. Specific, Chapter 2: Proteins BMPs 4 and 7 were significantly overexpressed, suggesting that these cells are being driven to maintain the calcifying phenotype. Cell signaling involving survival pathways is active when the analysis observed MAPK and AKT phosphorylations, indicative of cellular cytoskeleton dynamics and rearrangement. Furthermore, during the contractile-calcifying transition phenotype of VSMCs, the epigenetic machinery was finely modulated, requiring the translocation of DNMT3B and TET2 to the nucleus and which led us to assess whether the methylation profile of osteogenesis-related gene promoters can contribute to this process. By identifying the changes in the 5meC/5hmeC ratio, we showed more specifically the significance of the epigenetic modulation of the gene promoters related to BSP (bone sialoprotein) and Osterix, showing a positive correlation between the epigenetic signature of their gene promoters and the immediate transcripts. Chapter 3: The decrease in protein content and gene transcripts of a-SMA points once again to the loss of VSMC contractile function. The mechanism of histone modification was positively modulated when a significant increase in the protein content of HAT and PCAF acetyltransferases and H3K9ac at 72h was observed, as well as an overexpression of HDAC desacelisases 4 and 6. The action of SIRT 1 was investigated including the action of agonist (Resveratrol, a natural-obtained flavonoid) and antagonist (EX-527) and an increase in DNA methylation was observed, suggesting a positive action of this enzyme in the process of calcification of VSMC. Altogether, our results show for the first time the importance of the epigenetic mechanism in modulating osteogenic gene reprogramming markers during the acquisition of calcifying VSMCs the phenotype, which may drive the etiology vascular ectopic calcification, and as part of those enzymes is drugable it might support the development of new strategies to prevent this condition.